Effects of methamphetamine use on the children of users - Downey, Jade. (My University, 2007)
Methamphetamine use among users with children is becoming an epidemic in society. This study examined attitudes regarding primary caregiver methamphetamine use and the effects on their children by surveying approximately 20 Alcohol and Other Drug Abuse (AODA) counselors located in Western Wisconsin. It was hypothesized that AODA counselors would consider methamphetamine use as child abuse and believe families should remain intact while efforts are being made to overcome the addiction. Results indicated that the majority of participants believe that primary caregiver methamphetamine use is considered child abuse and that such occurrences should be reported. Many of those surveyed felt that children and caregivers should remain united or be reunited if children had previously been taken into protective services. Implications for future researchers would be to develop a broader survey instrument and use a larger sample.
Keywords: Methamphetamine abuse--Wisconsin; Methamphetamine--Wisconsin; Children of drug addicts--Wisconsin--Social conditions; Drug addicts--Family relationships--Wisconsin; Child welfare--Wisconsin